1992
DOI: 10.1089/aid.1992.8.1147
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Two Neutralizing and 8 Non-Neutralizing Epitopes on Simian Immunodeficiency Virus Envelope Using Monoclonal Antibodies

Abstract: Ten new monoclonal antibodies (MAbs) to SIV envelope were produced and characterized. Using a panel of 28 MAbs, 10 antibody binding sites on SIV envelope protein were identified. Seven sites were located in gp120 and three in gp41. Five sites in gp120 and two in gp41 were defined by overlapping peptides. The remaining two sites on gp120 and one on gp41 were distinguished by competition binding assays but could not be defined by overlapping peptides, suggesting that they were discontinuous or conformational epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
85
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(91 citation statements)
references
References 23 publications
6
85
0
Order By: Relevance
“…Regions coding for peptides to be expressed as CFPs were synthesized as PCR fragments designed with terminal NheI sites which allow insertion into the NheI, SpeI and XbaI sites of the vectors. All SIV envelope-coding sequences were taken from the SIVmac32H(pJ5 ) molecular clone (Rud et al, 1992) and all DNA insertions were checked by sequence analysis. Fusion proteins were expressed in E. coil and particles purified as described previously .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regions coding for peptides to be expressed as CFPs were synthesized as PCR fragments designed with terminal NheI sites which allow insertion into the NheI, SpeI and XbaI sites of the vectors. All SIV envelope-coding sequences were taken from the SIVmac32H(pJ5 ) molecular clone (Rud et al, 1992) and all DNA insertions were checked by sequence analysis. Fusion proteins were expressed in E. coil and particles purified as described previously .…”
Section: Methodsmentioning
confidence: 99%
“…After a further 1 h incubation at 37 °C, the plates were washed and developed with an enzyme substrate as previously described . Reactivity of the mouse anti-SIV V2 monoclonal antibody (MAb) KK13 (Kent et al, 1991(Kent et al, , 1992 with V2 peptides expressed in CFPs was assayed by a modified double-antibody sandwich ELISA (Voller et al, 1976). Guinea-pig polyclonal antiHBcAg serum (100-fold dilution) was used to capture serial dilutions (starting from 100 Ixg/ml) of CFPs in PBS/2% dried milk powder.…”
Section: Methodsmentioning
confidence: 99%
“…According to recent reports, the V3 analogous region of SIVm~o does not contain neutralizing epitopes. Instead, in addition to a conformation-dependent epitope (Kent et al, 1992), a neutralizing epitope was located in the V2 equivalent region comprising amino acid positions 171 to 189 (Kent et at., 1992;Benichou et al, 1992) corresponding to peptides 15 and 16. Interestingly, only the animal receiving the recombinant VV with two amino acid changes in peptide 15 exhibited a reactivity against both peptides, whereas the macaques immunized with sequence-homologous virus-derived gpl30 reacted only In conclusion, the administration of a virus-derived and a recombinant SIVm, , gpl30 vaccine has revealed that the antibody recognition patterns vary considerably.…”
Section: Discussionmentioning
confidence: 99%
“…Peptide 170-193 maps to the V2 domain which for SIV (Kent et al, 1992) and HIV-1 (Fung et al, 1992;McKeating et al, 1993) contains neutralization-sensitive epitopes. In the case of HIV-1, neutralization through this domain is not strain specific and the CBL22 peptide Fig.…”
Section: Neutralization-sensitive Domains On Hiv-2 Glycoproteinsmentioning
confidence: 99%